Short-term power-forecasting method of distributed PV power system for consideration of its effects on load forecasting - Liu, Yu; Li, Zhi; Bai, Kai; Zhang, Zhaoguang; Lu, Xining; Zhang, Xiaomeng (Journal of engineering (Stevenage, England), 2017)
This study analyses the distributed photovoltaic (PV) power system effects on common short-term load forecasting, based on the proposed power penetration index, and load data reconfiguration method, by using common short-term load-forecasting algorithm under conditions of the distributed PV power system and the power penetration index as 0, 5, 10, 15, 20, 24.46, 30, 35, 40, 50, 60 and 75%, the short-term load-forecasting accuracy obviously decreases. In this research study, the short-term power-forecasting method is proposed in order to offset the power output of distributed PV power systems, and transfer to the original load without the effects of distributed PV power systems or treated as the input information for updated load-forecasting model, this study proposes the short-term power-forecasting algorithm based on the BP neutral network for the typical distributed PV power system through training and validation of the proposed model. The power-forecasting accuracy is analysed and verified for a typical distributed PV power system, and the proposed method is effective in improving the accuracy for load forecasting.